2017
DOI: 10.17261/pressacademia.2017.537
|View full text |Cite
|
Sign up to set email alerts
|

Critical factors for oil palm plantation workers acceptance and use of mechanization technovation tools

Abstract: Oil palm plantation workers, still rely on manual tools and using mechanization technovation tools has been big issues as they rejected to use. Thus, in emphasizing technovation tools in a human activity, this study aims to examine several factors influencing acceptance and use technovation machine tools in Malaysia based on the revised Unified Theory of Acceptance and Use of Technology (UTAUT) model. A total of 126 oil palm plantation workers answer the questionnaire. This model was analyzed using SPSS techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This study shows the availability of mechanized technologies that have shown their efficiency in cutting, lifting, and collecting oil palm bunches, such as motorcycle trailers, grabbers, and minitractors with trailer, grabber and cableway systems (Alfonso et al, 2009b(Alfonso et al, , 2009aMahadi et al, 2018;Shuib et al, 2011Shuib et al, , 2020. However, the results also show low adoption of the most efficient technologies; the difficulty in mechanizing FFB harvesting processes is evident in studies conducted in Malaysia (Nawi et al, 2015;Norhajijah et al, 2021). This difficulty has been related to soil characteristics, funding availability, area of operation of these technologies, and crop yield, among other factors (Mosquera-Montoya et al, 2023).…”
Section: Harvestmentioning
confidence: 84%
See 1 more Smart Citation
“…This study shows the availability of mechanized technologies that have shown their efficiency in cutting, lifting, and collecting oil palm bunches, such as motorcycle trailers, grabbers, and minitractors with trailer, grabber and cableway systems (Alfonso et al, 2009b(Alfonso et al, , 2009aMahadi et al, 2018;Shuib et al, 2011Shuib et al, , 2020. However, the results also show low adoption of the most efficient technologies; the difficulty in mechanizing FFB harvesting processes is evident in studies conducted in Malaysia (Nawi et al, 2015;Norhajijah et al, 2021). This difficulty has been related to soil characteristics, funding availability, area of operation of these technologies, and crop yield, among other factors (Mosquera-Montoya et al, 2023).…”
Section: Harvestmentioning
confidence: 84%
“…Due to its inherent nature, the harvest stage demands sophisticated equipment, leaving few alternatives available for machinery and adopted systems. Enhancing the humanmachine interface is crucial during product design, and manufacturers must actively disseminate information and provide training to workers (Nawi et al, 2015). As suggested by Ramli et al (2021) and Syarifudin and Zareen (2021), a Manufacturing Powerhouse with expertise in developing and marketing high-capital equipment is also needed to bridge the gap between research, development, and technology adoption in plantations.…”
Section: Harvestmentioning
confidence: 99%
“…Feedback from oil palm growers indicates that modern technology has changed the management and operation of oil palm cultivation to increase productivity. Mohd Nawi et al (2018) clarified that the technology used in harvesting oil palm bunches includes collecting loose oil palm fruits, transferring the harvest to lorries for transportation to the factory while the technology for application in field operations includes fertilizer application, pest and disease control, and the cutting of palm fronds. Such applications of technological innovations have contributed immensely to the development of the palm oil sector in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%